The many faces of glioblastoma: Pictorial review of atypical imaging features. Issue 1 (February 2021) - Khandwala, Kumail; Mubarak, Fatima; Minhas, Khurram
Glioblastoma is an aggressive primary central nervous system tumour that usually has a poor prognosis. Generally, the typical imaging features are easily recognisable, but the behaviour of glioblastoma multiforme (GBM) can often be unusual. Several variations and heterogeneity in GBM appearance have been known to occur. In this pictorial essay, we present cases of pathologically confirmed GBM that illustrate unusual locations and atypical features on neuroimaging, and review the relevant literature. Even innocuous-looking foci, cystic lesions, meningeal-based pathology, intraventricular and infra-tentorial masses, multifocal/multicentric lesions and spinal cord abnormalities may represent GBM. We aim to highlight the atypical characteristics of glioblastoma, clarify their importance and list the potential mimickers. Although a definitive diagnosis in these rare cases of GBM warrants histopathological confirmation, an overview of the many imaging aspects may help make an early diagnosis.